Interprofessional Education: Students' Learning of Joint Patient Care - Anita Carin Gudmundsen; Bente Norbye; Madeleine Abrandt Dahlgren; Aud Obstfelder (Professions and Professionalism, 2018)
This study examines how patient care is developed in meetings between students of occupational therapy, physiotherapy, nursing and medicine who are allowed to shape their own interprofessional collaboration. We conduct a thematic interpretative analysis of audio recordings and observations from the meetings and informal talks with the students. The analysis draws on traditions in sociocultural learning theory that deal with interaction on something in common between actors with different knowledge bases and the consequences of this interaction. The analysis showed that the students developed collaboration in patient care by sharing, assessing and determining professional knowledge of patients’ health conditions collectively. In conclusion, we argue that the students learned to use a multiprofessional knowledge base in the design of patient treatment when they were given responsibility to create the collaboration themselves. This demonstrates that students can be encouraged to independently develop professional collaboration in patient care within interprofessional education.